Intramolecular hydrogen abstraction in radicals derived from inositol 1,3-acetals: efficient access to cyclitols - Murali, Chebrolu; Gurale, Bharat P.; Shashidhar, Mysore S. (European Journal of Organic Chemistry, 2010)
The benzylidene acetals obtained by cleavage of the orthobenzoate moiety in myo-mositol 1,3,5-orthobenzoate were used to prepare mono- as well as di-deoxy inositol derivatives via their xanthates. The dideoxygenation is a result of intramolecular abstraction of the benzylidene acetal hydrogen and subsequent cleavage of the acetal ring. Such a cleavage does not take place in analogous acetals derived from other orthoesters. The 1,3-acetals derived from myoinositol 1,3,5-orthoesters were also used to prepare neo-inositol and isomeric deoxy-amino inositols, Most of the reactions in these synthetic sequences starting from myo-inositol give one product in each step. The results presented here show that myo-inositol 1,3,5-orthobenzoate offers many advantages over other orthoesters for the synthesis of cyclitol derivatives from myo-inositol.
Keywords: cyclitols; Deoxygenation; Inosamine; Inositol; Radical reactions; Radicals; Xanthate

Thermal epimerization of inositol 1,3-benzylidene acetals in the molten state - Gurale, Bharat P.; Krishnaswamy, Shobhana; Vanka, Kumar; Shashidhar, Mysore S. (Tetrahedron, 2011)
1,3-O-Benzylidene-2,4,5,6-tetra-O-substituted-myo-inositol derivatives obtained by the DIBAL-H reduction of the corresponding myo-inositol 1,3,5-orthobenzoate derivatives undergo epimerization at the acetal carbon on heating, in the molten state, just above their melting point. The same epimerization reaction does not proceed either in the crystalline state or in solution. DFT calculations suggest that the epimeric acetal obtained by this thermal process is relatively more stable than the starting acetal. Either of these acetals could not be obtained by the reaction of the corresponding inositol derived diol with benzaldehyde. These observations constitute a novel reaction solely in the molten state, which are rarely encountered in the literature. X-ray crystal structures of the epimeric acetals as well as their radical deoxygenation reaction are also reported. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: cyclitols; Deoxygenation; Epimerization; Melt; Xanthate

Chiral crystals from an achiral molecule: 4,6-di-O-benzyl-1,3-O-benzylidene-2-O-(4-methoxybenzyl)-myo-5-inosose - Gurale, Bharat P.; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Acta Crystallographica Section C-Crystal Structure Communications, 2012)
The title achiral compound, C35H34O7, crystallizes in the chiral monoclinic space group P21. The molecules are densely packed to form a helical assembly along the crystallographic twofold screw axis via CH...O and CH...p interactions. Interestingly, the unit-translated helical chains are loosely connected via a rather uncommon edge-to-edge PhH...HPh short contact (H...H = 2.33 angstrom).

Radical mediated deoxygenation of inositol benzylidene acetals: conformational analysis, DFT calculations, and mechanism - Gurale, Bharat P.; Vanka, Kumar; Shashidhar, Mysore S. (Carbohydrate Research, 2012)
Xanthates of 1,3-benzylidene acetal derivatives of myo- and neo-inositols undergo dideoxygenation under Barton-McCombie conditions, as a result of intramolecular abstraction of the benzylidene acetal hydrogen and subsequent cleavage of the acetal ring. Scrutiny of structure of these bicyclic inositol derivatives shows that although the conformation of the two rings can vary depending on the configuration of the inositol ring and the phase in which the molecules are present, both the xanthates lead to the formation of the same dideoxyinositol. DFT calculations on these molecular systems suggest that neo-inositol derivatives undergo conformational change prior to radical formation while myo- inositol derivatives undergo conformational change subsequent to radical formation, during the deoxygenation reaction. A low barrier for intramolecular hydrogen transfer supports the extreme facility of this deoxygenation reaction. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Deoxygenation; DFT; Inositol; Mechanism; Radical; Xanthate

Synthesis of the aminocyclitol units of (-)-hygromycin a and methoxyhygromycin from myo-inositol - Gurale, Bharat P.; Shashidhar, Mysore S.; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2012)
Concise and efficient syntheses of the aminocyclitol cores of hygromycin A (HMA) and methoxyhygromycin (MHM) have been achieved starting from readily available myo-inositol. Reductive cleavage of myo-inositol orthoformate to the corresponding 1,3-acetal, stereospecific introduction of the amino group via the azide, and resolution of a racemic cyclitol derivative as its diastereomeric mandelate esters are the key steps in the synthesis. Synthesis of the aminocyclitol core of hygromycin A involved chromatography in half of the total number of steps, and the aminocyclitol core of methoxyhygromycin involved only one chromatography.

Myo-Inositol 1,3-acetals as early intermediates during the synthesis of cyclitol derivatives - Gurale, Bharat P.; Sardessai, Richa S.; Shashidhar, Mysore S. (Carbohydrate Research, 2014)
Synthetic sequences starting from commercially available myo-inositol necessarily involve protection-deprotection strategies of its six hydroxyl groups. Several strategies have been developed/attempted over the last several decades leading to the synthesis of naturally occurring phosphoinositols, their analogs, and cyclitol derivatives. Of late, myo-inositol 1,3-acetals, which can be obtained by the reductive cleavage of myo-inositol orthoesters have emerged as early intermediates for the synthesis of phosphorylated and other inositol derivatives. This mini-review is an attempt to illustrate the economy and convenience of using myo-inositol 1,3-acetals as early intermediates during syntheses from myo-inositol. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Acetal; Cyclitol; Inositol; Protecting group; Signal transduction

Inositol to aromatics -benzene free synthesis of poly oxygenated aromatics - Gurale, Bharat P.; Shashidhar, Mysore S.; Sardessai, Richa S.; Gonnade, Rajesh G. (Carbohydrate Research, 2018)
A method for the preparation of benzene derivatives from myo-inositol, an abundantly available phyto chemical is described. 1,3-Bridged acetals of inososes undergo step-wise elimination leading to the formation of polyoxygenated benzene derivatives. This aromatization reaction proceeds through the intermediacy of a beta-alkoxyenone, which could be isolated. This sequence of reactions starting from myoinositol, provides a novel route for the preparation of polyoxygenated benzene derivatives including polyoxygenated biphenyl. This scheme of synthesis demonstrates the potential of myo-inositol as a sustainable non-petrochemical resource for aromatic compounds. (C) 2018 Elsevier Ltd. All rights reserved.